The Relationship between Body Shape Dissatisfaction and Self-Confidence in Female Students at SMAN 1 Cikampek - Haryati, Aisyah; Irma Sari Marbun, Indah; Syarifuddin, Assyaif (International Journal of Social Science, Education, Communication and Economics, 2024)
The aim of this research was to examine the relationship between body shape dissatisfaction and self-confidence among female students at SMAN 1 Cikampek. This research was conducted on class X students of SMAN 1 Cikampek, totaling 162 students. The sampling method used was random sampling. The measuring instrument used is a scale of self-confidence and dissatisfaction with body shape based on the Likert scale model. Validity and correlation tests use product moment with a significance level of 0.05. To test the validity, rit is used. The self-confidence scale consists of 25 valid items with a validity coefficient ranging from 0.395 – 0.908 and a reliability coefficient of 0.920 (>0.9), very reliable criteria. The body shape dissatisfaction scale consists of 19 valid items with a validity coefficient ranging from 0.313 – 0.719 and a reliability coefficient of 0.780. The results of the two variable correlation tests show a negative relationship between body shape dissatisfaction and self-confidence with a bivariate coefficient of Rˣʸ=-0.335 with p=0.000 (p<0.05). Thus, Ha is accepted and H0 is rejected. Based on the research results, it can be concluded that there is a relationship between form dissatisfaction and self-confidence in a negative direction for class X female students at SMAN 1 Cikampek.